Design of PP/EPDM/NBR TPVs with tunable mechanical properties via regulating the core-shell structure. (October 2020) - Peng, Tao; Lv, Fei; Gong, Zhou; Cao, Liming; Yan, Xuesong; Ge, Ling; Abubakar, Saifudin; Chen, Yukun
Abstract: In this work, polypropylene (PP)/ethylene-propylene-diene monomer (EPDM)/butadiene acrylonitrile rubber (NBR) TPVs with different EPDM/NBR ratios were prepared by the core-shell dynamic vulcanization. The relationship between the core-shell structure and mechanical properties of the TPVs were thoroughly investigated. The formation of core-shell structure by adding NBR is conducive to the mechanical properties of the TPVs. The ratio of EPDM to NBR has an important effect on the structure and performances of the final products, and there is a critical ratio for this effect change. Transmission electron microscope (TEM), tensile test, reprocessing test, ageing test, rheological behavior test and stress relaxation were used to characterize the morphology and properties of the TPVs in detail. It was found that when the ratio of EPDM/NBR was 2:4, the tensile strength increased by 14% compared with PP/EPDM TPV without NBR. Meanwhile, the reprocessing properties, rheological characteristics and instantaneous tensile deformation, etc. all exhibited sudden changes at this critical ratio. Graphical abstract: Image 1 Highlights: Core-shell structure with EPDM as the shell and NBR as the core was formed in the PP/EPDM/NBR ternary TPV. There is a critical rubber ratio to form perfect core-shell structure. The relationship between core-shell structure and the mechanical properties were studied thoroughly. The mechanical properties could be further regulated by changing the ratios of the rubber phases. The core-shell structure could also affect the aging performances of the TPVs.